PERBEDAAN HEALTH BELIEF MAHASISWA PEROKOK UNIVERSITAS ESA UNGGUL BERDASARKAN JENIS KELAMIN - Noviyanto, Simon; Wijaya, Yeny Duriana (Jurnal Psikologi, 2016)
AbstractSmoking behavior was discovered at EsaUnggul University. Students who do the smoking behavior is not only men but also women. Students of male smokers, smoking is considered reasonable thing to do, while smoking for female students, smoking assessed a way to look attractive. Female smokers believed the threat of disease from smoking will interfere with student health than male smokers. Ones beliefs on health-related behaviors called health belief. Purpose of this study was to determine differences health belief EsaUnggul University student smokers. Research includes a comparative study non-experimental. Amount 100 sample students smokers. With data retrieval technique of non-probability sampling with purposive sampling.Health measuring devices belief (valid item 33) with reliability coefficient of 0.940. Statistical results, obtained by the Sig. (2-tailed) or 0.000 (p <0.05) with a mean value of a group of male smokers student at 89.30 and the mean value of female smokers student produces mean deference by 93.56 -4.26 , There are differences health belief between student EsaUnggul University gender male and female smokers. Keywords: health belief, smoking behavior, student AbstrakPerilaku merokok masih ditemukan di Universitas esa unggul. Mahasiswa yang melakukan perilaku merokok bukan hanya laki-laki, namun juga perempuan. Bagi mahasiswa perokok laki-laki, merokok dinilai wajar untuk dilakukan, sedangkan perilaku merokok bagi mahasiswa perempuan, merokok dinilai sebagi cara untuk terlihat menarik. Mahasiswa perokok perempuan lebih meyakini ancaman penyakit dari perilaku merokok akan mengganggu kesehatannya daripada mahasiswa perokok laki-laki. Keyakinan seseorang terhadap perilaku yang berhubungan dengan kesehatan disebut dengan health belief. Tujuan penelitian ini adalah untuk mengetahui perbedaan health belief mahasiswa perokok Universitas Esa Unggul berdasarkan jenis kelamin. Penelitian ini termasuk studi komparatif non-eksperimental. Jumlah sampel penelitian 100 mahasiswa perokok. Dengan teknik pengambilan data non-probability sampling dengan jenis purposive sampling. Alat ukur health belief (33 aitem valid) dengan koefisiensi reabilitas 0,940. Hasil uji statistik, diperoleh nilai Sig.(2-tailed) 0.000 atau (p < 0.05) dengan nilai mean dari kelompok mahasiswa perokok laki-laki sebesar 89,30 dan nilai mean dari mahasiswa perokok perempuan sebesar 93,56 menghasilkan mean deference -4.26. Terdapat perbedaan health belief antara mahasiswa perokoko laki-laki dan mahasiswa perokok perempuan. Kata kunci :health belief, perilaku merokok, mahasiswa.